Changing faces in the Spirituality of Christ Apostolic Church - Oluwasanmi , Johnson Olusola; Ogunbiyi , David Oluwabukunmi; Adedibu, Babatunde A. (Corpus Intellectual, 2024)
Christ Apostolic Church (CAC) is an African Indigenous Church (AIC) which was formally registered in 1947 but had been in existence since 1918 as a prayer group known as Egbe Aladura (Prayer Society) which metamorphosed into several other names over the years before 1947. The study aims to assess whether the contemporary CAC maintains the unique spirituality that distinguishes it from other AICs. The research adopts a historicalcritical approach with a focus on spirituality, investigating the historical origins of faith and spirituality among selected founding Fathers of CAC in comparison to present-day practices, specifically within CAC in Babalola Region in Oyo state in CAC demographical spread. Data collection involved participant-observation methods, gathering first-hand information on doctrinal emphases and spiritual practices from past and current CAC members in Babalola Region. Questionnaires were administered to 535 selected members and ministers from different District Coordinating Councils (DCCs) and Zones, while interviews were conducted with fivepersons who are Pastors and leaders within Christ Apostolic Church. Secondary data sources such as literature reviews, church publications, magazines, dictionaries, learned journals, and online sources were consulted. Findings reveal a decline in adherence to early spiritual practices by contemporary CAC members compared to its inception. Moreover, clergy members have not adequately addressed this deviation from traditional spirituality, indicating a decline in spiritual quality within the church community. To address this issue, it is recommended that comprehensive teachings grounded in biblical principles be provided for both current and new members rather than focusing solely on customs or rituals. In addition, the development of a national manual similar to existing Sunday school materials can assist in promoting spiritual growth.